2021
DOI: 10.3390/cancers13051090
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cancers with High Grade Tumor Budding Exhibit Hallmarks of Diminished Anti-Tumor Immunity

Abstract: Tumor budding is associated with epithelial-mesenchymal transition and diminished survival in a number of cancer types including pancreatic ductal adenocarcinoma (PDAC). In this study, we dissect the immune landscapes of patients with high grade versus low grade tumor budding to determine the features associated with immune escape and disease progression in pancreatic cancer. We performed immunohistochemistry-based quantification of tumor-infiltrating leukocytes and tumor bud assessment in a cohort of n = 111 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…Our study demonstrated the positive correlation between high-grade tumor budding and PD-L1 expression on TCs. This finding is supported by a recent study by Sadozai et al, which demonstrated that extensive tumor budding is accompanied by diminished anti-tumor immunity and higher B7-H3 (CD276) expression [ 33 ]. In colorectal cancer, high-grade tumor budding is associated with an up-regulation of negative regulatory immune checkpoints and immune evasion [ 34 ].…”
Section: Discussionsupporting
confidence: 68%
“…Our study demonstrated the positive correlation between high-grade tumor budding and PD-L1 expression on TCs. This finding is supported by a recent study by Sadozai et al, which demonstrated that extensive tumor budding is accompanied by diminished anti-tumor immunity and higher B7-H3 (CD276) expression [ 33 ]. In colorectal cancer, high-grade tumor budding is associated with an up-regulation of negative regulatory immune checkpoints and immune evasion [ 34 ].…”
Section: Discussionsupporting
confidence: 68%
“…Additionally, we conducted a measurement of YY1 expression levels in patients exhibiting varying TB grades. TB refers to the presence of dedifferentiated tumor cells, which can manifest as solitary cells or small clusters containing up to four cells located at the invasive frontier of diverse cancers [ 28 ]. It is well-documented that TB is linked to EMT and reduced survival rates.…”
Section: Resultsmentioning
confidence: 99%
“…In the equation, i represents the grade of staining intensity, which includes no staining ( i = 0), weak ( i = 1), moderate ( i = 2), and strong ( i = 3); p i represents the percentage of labeled tumor cells with the corresponding stating intensity. To quantify immune cell infiltration, positive cells in the tumoral and stromal compartments were enumerated separately and normalized per unit area as cells/mm 2 …”
Section: Methodsmentioning
confidence: 99%
“…To quantify immune cell infiltration, positive cells in the tumoral and stromal compartments were enumerated separately and normalized per unit area as cells/ mm 2 . 13…”
Section: Immunohistochemical Staining (Ihc) With Tmamentioning
confidence: 99%